Collective memory and ethnic discrimination in Soe Tjen Marching’s Dari Dalam Kubur: A genetic structuralism analysis - Salsabila Davina Shiekha; Nanang Endrayanto (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2025)
Soe Tjen Marching’s Dari Dalam Kubur portrays the experiences of survivors of the 1965 tragedy and the ethnic discrimination faced by Chinese Indonesians. Focusing on trauma and memory, this study examines how the novel represents survivors’ collective memory and state-driven discrimination through the lens of Lucien Goldmann’s genetic structuralism. Using qualitative textual analysis, the study reveals a persistent tension between remembering and forgetting, reflecting the enforced silence imposed on survivors. Discrimination against Chinese Indonesians is depicted as systematic oppression reinforced through social and institutional segregation. The findings demonstrate how literary narratives function as sites of collective memory by establishing homological relationships between textual structures and socio-historical realities. The study concludes that Dari Dalam Kubur articulates a collective worldview in which memory operates as a form of resistance and identity functions as a source of dignity.